Pandangan K. H. Husein Muhammad tentang Pernikahan Dini dan Implikasinya terhadap Remaja Madrasah Tsanawiyah - Mazroatus Sa’adah; Sholikah Sholikah (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze K. H. Husein Muhammad’s views on the practice of early marriage and to identify the factors influencing its occurrence among Madrasah Tsanawiyah adolescents, as well as its implications for their attitudes, understanding, and behavior. Employing a descriptive qualitative approach, this research utilizes library studies on the works and thoughts of K. H. Husein Muhammad, complemented by documentation and supporting interviews to explore in depth the construction of this religious scholar’s ideas regarding early marriage and their relevance to adolescent education. Research informants included the head of the madrasah, Islamic Education teachers, and three students selected through purposive sampling. Interview results show that the head of the madrasah and Islamic Education teachers view K. H. Husein Muhammad’s emphasis on the principles of public welfare (maslahah), gender justice, and child protection in the framework of progressive fiqh as highly relevant educational foundations for preventing early marriage within the MTs environment. Factors contributing to early marriage among adolescents include socio-cultural conditions, economic constraints, misconceptions about religious teachings, social media influence, promiscuity, and family pressure. Interviews conducted at MTs Al-Asyhar Karangagung, Palang, Tuban Regency indicated that the values embedded in his thoughts have been internalized through madrasah education, such as strengthening educational awareness and prioritizing the pursuit of knowledge, understanding mental, moral, and economic readiness, fostering critical attitudes toward early marriage, increasing awareness of gender justice, promoting religious moderation, and cultivating ethical social interactions. Overall, this study affirms that K. H. Husein Muhammad’s ideas hold significant relevance for educational efforts and the prevention of early marriage in madrasah settings, while also contributing to the development of a responsive fiqh perspective on contemporary adolescent issues.